The Ultrastructure of Toxoplasma gondii - Ferguson, D; Dubremetz, J (Elsevier, 2013)
Electron microscopy has been an important tool for understanding the biology and ultrastructure of Toxoplasma gondii. As an obligate intracellular parasite, T. gondii has evolved specialized organelles for invasion and successful intracellular parasitism. Early electron microscopy studies identified the unique ultrastructural features of the secretory organelles of the various invasive forms of T. gondii. These studies also illuminated the features of the parasitophorous vacuole and intracellular development of T. gondii, as well as the development of the parasite during the sexual cycle and during formation of the latent bradyzoite forms. This chapter reviews the key ultrastructural features of T. gondii life cycle forms using an extensive collection of micrographs provided by the authors. © 2014 Elsevier Ltd. All rights reserved.